Estimation of carbon balance components for an agricultural landscape in South Korea - Steve, Lindner; Bora, Lee; Janine, Kettering; Peng, Zhao; Bumsuk, Seo; Ochuodho, Dennis O.; Gian-Reto, Walther; John, Tenhunen (My University, 2011)
The goal of our work is to evaluate as far as possible carbon budget components for an agriculturally dominated landscape in South Korea. In the last decades, rapid changes of land use and land cover due to economic development after the Korean War (Kim and Park, this proceedings) has certainly led to large changes in atmospheric CO2 exchange in the Haean Catchment in Gangwon Province, South Korea. Our studies represent a first step in trying to understand this change at landscape scale. We hypothesized that crops differ in their CO2 assimilation rates and also in their patterns of C allocation, thereby influencing the general patterns of CO2 exchange and production. To test these ideas, we quantified the seasonal patterns of NEE, GPP and Reco in non-irrigated, rain-fed crop fields (radish, potato, cabbage, bean) and in irrigated rice paddies during the growing seasons 2009 and 2010. It was shown that the most important climate factors for gas exchange and biomass development (radiation, temperature, precipitation) were very similar between locations within the catchment. After planting of the crops, the maximum GPP for potato and cabbage is reached in mid-June with up to 70 and 60 µmol m-2 s-1, respectively. A similar trend in the increase of GPP for rice, radish and bean with parallel development of plant biomass is evident. Significant differences in the maximum GPP between rice, radish, and bean occur in mid-August with fluxes up to 20, 40 and 55 µmol m-2 s-1, respectively. Harvest data on crop yields are reported. Future work is oriented to establishing the links between carbon gain, plant growth and yield; as well as up-scaling the plot results to landscape level.
Keywords: crop gas exchange; net ecosystem; CO2 exchange; ecosystem respiration; gross primary production; allocation; agricultural yield